2003
DOI: 10.2337/diabetes.52.2.356
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Insulin Secretion by Denatonium, One of the Most Bitter-Tasting Substances Known

Abstract: Denatonium, one of the most bitter-tasting substances known, stimulated insulin secretion in clonal HIT-T15 ␤-cells and rat pancreatic islets. Stimulation of release began promptly after exposure of the ␤-cells to denatonium, reached peak rates after 4 -5 min, and then declined to near basal values after 20 -30 min. In islets, no effect was observed at 2.8 mmol/l glucose, whereas a marked stimulation was observed at 8. M ultiple signal transduction mechanisms in taste cells detect sweet, sour, bitter, salty, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
(31 reference statements)
2
20
0
Order By: Relevance
“…10. In agreement with this model, a previous study (69) indicated that DB does not exert any direct effect on L-type VSCC activity. It is interesting that the signaling cascade proposed in Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…10. In agreement with this model, a previous study (69) indicated that DB does not exert any direct effect on L-type VSCC activity. It is interesting that the signaling cascade proposed in Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, we also verified that pretreatment of STC-1 cells with glybenclamide (1 to 50 M) for 1 h had no effect on the subsequent increase in [Ca 2ϩ ] i induced by DB (data not shown). In contrast, a concentration of glybenclamide of 1 M was sufficient to mimic DB effects in HIT-T15 ␤-cells (69).…”
Section: Db and Ptc Elicit Rapid Increase In [Camentioning
confidence: 87%
See 1 more Smart Citation
“…The most conserved T2Rs (e.g., T2R1, T2R4, and T2R38) between human and rodents have known bitter trait or ligands [6-n-propylthiouracil (PROP)/sucrose octaacetate (SOA)/PTC]. DB is regarded as the bitterest substances perceived by human and is widely used in taste warning (4,25). Potential T2Rs that recognize DB include hT2R4 and mT2R108 and hT2R44 and mT2R120, as demonstrated by their sensitivity to DB in a heterologous expression system (5,22).…”
Section: Discussionmentioning
confidence: 99%
“…A good example for the fact that GI responses must not necessarily involve (bitter) taste-related signaling elements has been obtained in rat pancreatic tissue. Here, Straub et al [150] used the bitter substance denatonium benzoate to stimulate insulin release from clonal HIT-T15 β-cells as well as from isolated rat pancreatic islets. In the presence of denatonium, islets bathed in glucose solution start secreting insulin through a mechanism that does not involve gustducin or transducin as assessed in a trypsin digestion assay.…”
Section: Physiological Functions Of Gi Taste Receptorsmentioning
confidence: 99%